Kinetics and Mechanism of Hydrolysis of Di-S-Butyl Phosphorothioate via Conjugate Acid Species - Patil, R.; Shinde, C.P.; Samadhiya, A. (Asian Journal of Chemistry, 2010)
Di-S-butyl phosphorothioate has been made in acid region (0.1 to 7.0 mol dm–3) at 98ºC in 10% dioxane-water mixture (v/v). Ionic strength data up to 3.0 μ requires the participation of conjugate acid species and to determine theoretical rates. Theoretical rates, estimated from second empirical term of Debye-Hückel, have been found in close agreement with experimental rates. Bimolecular behaviour has been decided by the Arrhenius parameters and by the analysis of molecularity data. The phosphate diester involves P-S bond fission which is strengthened by comparative kinetic data.